Expanded resection in the canalicular route - Nin Vivó, Jorge; Brandolino, Mario V. (Cirugía del Uruguay, 1982)
Lobectomy with sleeve resection of main bronchus and pneumectomy including carina are the most frequent eníargements to the tracheo bronchial tree in lung cancer resection. Indications of lobectomy and sleeve resection are given. The ideal candidate is defined, as well as other situations. Most cases are performed in upper lobes. Pneumectomy enlarged to carina es seldom performed having high morbi-mortality therefore it may be indicated in selected patients. A multidisciplinary team including pathologists, anaesthesists must work coordinatively.